Screening history and risk of death from prostate cancer: a nested case–control study within the screening arm of the Finnish Randomized Study of Screening for Prostate Cancer (FinRSPC) - Talala, Kirsi; Walter, Stephen; Taari, Kimmo; Tammela, Teuvo L. J.; Kujala, Paula; Auvinen, Anssi (Cancer causes & control, 2024)
Purpose We assessed the risk of death from prostate cancer (PCa) in relation to men’s screening histories, i.e., screening attendance among men who were offered screening. Methods Men in the Finnish Randomized Study of Screening for Prostate Cancer (FinRSPC) screening arm were invited to up to three screening rounds with the serum prostate-specific antigen (PSA) test at 4-year intervals during 1996–2007. Case subjects ( n = 330) were men who died from PCa. Each case was matched to five controls ( n = 1544) among the men who were free of PCa. Screening history was defined as (1) never/ever attended screening prior to the case diagnosis; (2) attended at the first screening round; and (3) recency of screening, calculated as the time from last screening attendance to the date of case diagnosis. The association between screening history and the risk of death from PCa was estimated by odds ratios (OR) with 95% confidence intervals (CI) using conditional logistic regression. Results Having ever attended screening versus never attended was associated with a reduced risk of PCa death (OR 0.60, 95% CI 0.45–0.81) and a similar association was found for those attended (versus not attended) the first screening round (OR 0.67, 95% CI 0.51–0.87). The effect by time since last screen for the risk of PCa death was significantly lower 2–7 years since last screen. Conclusion Among men invited to screening, subjects who attended any PSA screening during the previous 19 years had a 40% reduction in PCa mortality compared to non-screened men.